Effect of arginine silicate inositol complex on bone mineralization - Şahin, Kazım; Onderci, M; Şahin, Nurhan; Balci, TA; Gursü, MF; Juturu, V; Küçük, Ömer (Federation Amer Soc Exp Biol, 2005)
[Abstract Not Available]
Experimental Biology 2005 Meeting/35th International Congress of Physiological Sciences -- MAR 31-APR 06, 2005 -- San Diego, CA